Mathematical morphology and its applications to signal and image processing : 14th International Symposium, ISMM 2019, Saarbrücken, Germany, July 8-10, 2019, Proceedings /: 14th International Symposium, ISMM 2019, Saarbrücken, Germany, July 8-10, 2019, Proceedings. (2019) - Unknown
No abstract available